AN IMAGE OF MYTH/THE MYTHIC VISION OF JOSEPH CAMPBELL - Pulak, David (Journal of Dharma, 1988)
The soul Aristotle observed, never thinks without images. Likewise, the child looks and recognizes before it can speak. What we subsequently see, or choose to see, determines how we think; in turn influencing how and what we see. But there is another sense in which sight precedes speech. While language establishes an idea of what the world is, we nevertheless are surrounded by images that words cannot describe.